Strategi Pengembangan Usaha pada Salsa Bakery dengan Pendekatan Analisis SWOT - Jordy Maulana Agusani; Hendra Sastrawinata; Dewi Fadila (Politeknik Negeri Sriwijaya, 2024)
This writing aims to produce a business development strategy and expand the market reach of this Salsa Bakery business. Salsa Bakery, a company engaged in the Bakery industry must conduct a thorough evaluation of internal and external factors that affect its business performance. The study used SWOT analysis to identify strengths, weaknesses, opportunities and threats at Salsa Bakery. The result of the analysis show that Salsa Bakery has strength in terms of high product quality, loyalty to customers and guaranteed cheap product prices. However, disadvantages include not having your own store to product on, limited production capacity and lack of human resources to promote products. Opportunities that can be utilized include the ability to create new variants or flavor that can attract more customer as well as the potential for expansion into the online market. While on other hand, the threats faced include fierce competition in the home Bakery product industry and fluctuations in raw material prices. Based on SWOT analysis, Salsa Bakery is proposed to leverage the power to increase production through investment in technology and expansion of production facilities, increasing operational efficiency and expanding distribution networks, exploring opportunities by developing innovative new variants or flavors and strengthening its presence in the online market, confronting threats with product diversification strategies and opening its own stores in strategic locations.